Designing inhalable metal organic frameworks for pulmonary tuberculosis treatment and theragnostics via spray drying. Issue 87 (7th October 2020) - Luz, Ignacio; Stewart, Ian E.; Mortensen, Ninell P.; Hickey, Anthony J.
Abstract : Inhalable metal organic framework (MOF) aerosols have been developed via spray drying as a therapy for multi-drug resistant (MDR) tuberculosis (TB). Abstract : Inhalable metal organic framework (MOF) aerosols have been developed via spray drying as a therapy for multi-drug resistant (MDR) tuberculosis (TB). The CuPOA2 (pyrazinoate acid) MOFs can be tailored to exhibit a respirable mass median aerodynamic diameter (MMAD) of 2.6 μm. This method is repeated to manufacture Gd0.1 Cu0.9 (POA)2 MOFs for inhalable theragnostics.